Stepping out of the magic circle : regulation of play/life boundary in MMO-mediated romantic relationship - Huynh, Kim-Phong (2014)
Massively multiplayer online role-playing games (MMOs) are spaces of socialization and relationship formation and maintenance. This qualitative study seeks to understand how MMO players delineate the boundary between play and life when it comes to their game-originated romance. A typology of players was devised to understand players' constructions of boundaries, and players' strategies against perceived stigma when moving their relationship offline were discussed. The findings call for a shift towards a more player-centric and pluralist conceptualization of the magic circle of play.